Hubungan Faktor Fisik Lingkungan Dan Pengelolaan Sampah Terhadap Indeks Populasi Lalat Di Resto Apung Pelabuhan Muara Angke Tahun 2022 - Atang Saputra; Putri Arvinanda; Syarifuddin (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The restaurant is a very potential place as a breeding ground for flies, so it requires monitoring the density of flies. Flies act as vectors of disease carriers. Diseases caused by flies such as diarrhea, cholera, and dysentery.One of the breeding places for flies is garbage or food scraps from processed products. Flies love the distinctive smell of rotting garbage. Therefore, waste has a big role in the spread of diseases, especially those that can be transmitted through food. Waste management is needed so that garbage does not accumulate in order to break the life cycle and breeding of flies. In addition, the behavior of the spread of flies is strongly influenced by the intensity of light, temperature, and humidity. Flies are also phototropic insects, which are light-loving. The effect of light on flies depends entirely on temperature and humidity. This study uses a cross-sectional survey study with a quantitative analytic approach. The population in this study amounted to 30 restaurants in Muara Angke Harbor. In this study, no sampling was carried out because it used the total of the entire population. The purpose of this study was to determine the relationship between physical environmental factors, namely light intensity, temperature, air humidity, and the stage of garbage collection to the fly population index at restaurants in Muara Angke Harbor. The results of the study showed that there was no significant relationship between light intensity and fly population index (p-value=1,000), temperature and fly population index (p-value=0.565), humidity and fly population index (p-value=0.534). There was a significant relationship between the waste collection stage and the fly population index (p-value=0.002).